Índice de nombres de los volúmenes 1 (1991) al 17/18 (204-2005) [a cargo de Esther Aguilar de la Torre, María Luisa Montaño Montero, Mónica Morcillo González, Jéssica Sánchez Espillaque] [pp. 229-381]. - -, - (Cuadernos sobre Vico, 2020)
Número 19-20, 2006-2007. 470 págs. ISBN 1130-7498